EMERGENCY AS A PROBLEM OF OUR TIME - V. P. Miroshnichenko; B. M. Goldovskiy (Сучасні медичні технології)
Abstract. The significance of the work is determined by the current situation in the modern world: climate change, accompanied by catastrophic consequences for humanity, including the coronavirus pandemic. All these phenomena provide grounds for considering and improving both the essence of the concepts of "emergency situation" and their definitions, which will make it possible to find mechanisms for the rational use of resources to compensate and/or prevent them. In accordance with this, the tasks were set: to compare the known definitions of emergency situations, to identify and clarify the relationship between the formulation of emergencies and their content, to clarify their relationship with disasters, to identify the main stages of their development, and general mechanisms that can allow them to more effectively resist them. It is proposed to revise the normative definition of an emergency situation.